Shariah-compliant cryptocurrency: Navigating opportunities and challenges at the intersection of Islamic finance and digital innovation - Dahlan, Olivia Putri (Journal of Islamic Economic Insights, 2025)
The emergence of cryptocurrencies, driven by technological advancements and the rise of electronic business (e-business), presents both opportunities and challenges for Islamic finance. Cryptocurrencies, such as Bitcoin, have introduced novel digital assets that facilitate fast, borderless, and secure transactions without traditional financial intermediaries. However, their compatibility with Islamic finance principles governed by Shariah law remains a subject of debate. While some scholars argue against cryptocurrencies because of speculation and lack of intrinsic value, others explore the potential for Sharia-compliant solutions backed by tangible assets. Despite challenges, such as regulatory uncertainty and value fluctuations, blockchain technology offers transparency and security, aligning with Islamic finance's emphasis on ethical and equitable dealings. Recommendations include continued research, the development of Shariah-compliant cryptocurrencies, education initiatives, regulatory clarity, and embracing innovation to enhance financial inclusion. By implementing these recommendations, Islamic finance can navigate the complexities of cryptocurrency integration, while upholding Shariah principles and fostering inclusive economic growth.